TRIBOLOGICAL IMPACTS OF TERTIARY FUELS ON LUBRICANT OIL IN DIESEL ENGINES - Muhammad Alam; Bahadr Yar Khan; Sher Muhammad Ghoto; Muhammad Panah; Sajjad Bhangwar; Rashid Ali Hakro; Muhammad Ramzan Luhur (Policy Research Journal, 2025)
This study explores the effects of a tertiary fuel, especially N-pentanol, when mixed with two common fuels, D100 (diesel) and B20 (a biodiesel blend), on the state and performance of lubricating oil after 25 and 50 hours of engine running. The study investigates the impacts of this tertiary fuel addition, with a focus on engine wear, lubricating oil quality, and potential benefits in fuel efficiency. The engine was run for 50 h on each fuel sample, and the data were taken and tested per 25 h for elemental analysis and physical properties of lubricant oil. The results manifest that the metal concentration found different elements in lubricant oil, i.e., Aluminium (4.704, 8.21), (2.492, 4.21) and (1.072, 2.492); Chromium (4.249, 4.602), (3.976, 4.173) and (1.764, 3.44); Iron (1.891, 2.647), (1.188, 1.794) and (0.864,1.015); Manganese (6.08, 10.07), (2.38, 4.396) and (1.69, 2.41) in diesel, biodiesel-blended fuel, and biodiesel blended with N-pentanol, respectively. This study found that biodiesel-blended fuel and N-pentanol have lower metal concentrations than diesel, resulting in longer engine life. This study reveals how N- pentanol, as a tertiary fuel, impacts lubricating oil performance, influencing wear patterns, additive interactions, and contaminant presence. Assessing compatibility with D100 and B20, it explores N-pentanol's ability to enhance engine performance. The findings contribute to understanding how tertiary fuels, like N-pentanol, may alter lubricating oil behavior over extended durations. Implications include improved compression ignition engine performance, extended component lifespan, and increased use of alternative, sustainable fuels.